Gender and Employee Experience: Uncovering the Factors that Matter Most - Trajkova, Kate; Mileva, Ivona; Andonova, Marija; Jordanova, Peshevska Dimitrinka (Archives of Business Research, 2025)
Understanding the factors that drive employee experience is crucial for fostering a productive and inclusive work environment. In an era where employee experience is a critical determinant of organizational success, understanding how gender impacts this experience is essential. This article aims to study the gender differences in factors influencing employee experience, utilizing data collected from a structured questionnaire administered to a diverse workforce. By examining variations in responses across different gender groups, the study identifies significant patterns and disparities in how employees perceive and interact with their work environments. The findings underscore the importance of tailoring organizational practices to address gender-based needs and preferences, thereby fostering a more inclusive and supportive work environment. This research offers valuable recommendations for organizations seeking to enhance employee engagement and satisfaction through gender-sensitive approaches.